Implementation of KPU's Digital Systems in the 2024 General Election: A Case Study of SIPOL, SILON, and SIREKAP in South Sumatra Province - M. Albahori; Sunarto; Gatot Hery Djatmika; T. Herry Rachmatsyah (CV. Syntax Corporation Indonesia, 2025)
This study analyzes the implementation of digital election policy by the General Elections Commission (KPU) of South Sumatra Province during the 2024 Simultaneous Elections, focusing on the SIPOL, SILON, SIDALIH, and SIREKAP systems. Using a qualitative descriptive approach with a case study design, data were gathered through in-depth interviews with KPU officials, system developers, and election observers, as well as from official documents, media, and academic sources. Data analysis employed the Miles and Huberman interactive model, supported by triangulation and member checking for validity. Findings show that SIPOL and SILON have successfully improved efficiency and transparency in political party and legislative candidate registration. However, SIREKAP faces challenges in accuracy, limited human resources, and unequal infrastructure. Additional obstacles include organizational resistance to change, weak inter-agency coordination, and low grassroots digital literacy. Internal support from KPU structures and external backing from local governments, Bawaslu, political parties, civil society, and media are vital for sustaining digital policy. The study concludes that digital transformation in elections depends not only on technological innovation but also on stakeholder collaboration, human resource readiness, and adaptive institutional governance. South Sumatra’s experience illustrates broader national challenges in advancing digital democracy, emphasizing the need for comprehensive reform and strengthened institutional capacity.